Biomaterials for Bone Tissue Regeneration Extracted from Fish Wastes - Anaya-Barajas, D.; Aguilar-Pliego, J.; González-Vélez, V.; Vélez-Tirado, M. (Revista Mexicana de Ingenieria Biomedica, 2019)
Biomaterials for bone tissue regeneration are commonly based in the natural design of bone where the stiffness of a ceramic material as hydroxyapatite is combined with the flexibility of a polymer such as collagen. Both materials can be extracted from human consumed fish waste, such as scales, bones and skin. The recovery of these bioma-terials from fish waste has the advantage of yielding natural materials of low toxicity, avoiding the possible disease transmission found for the collagen coming from mammalians. In this article, we review several reports about colla-gen type I and hydroxyapatite precursors extraction, and composite synthesis, from fish waste in order to propose these methods as a green alternative for biomaterials useful for medical purposes.